Nilai Ryosai (Good Wife) Zaman Edo dalam Novel Gadis Pantai Karya Pramoedya Ananta Toer (2000) - Annisa Maulida Salamah (Janaru Saja: Jurnal Program Studi Sastra Jepang (Edisi Elektronik), 2020)
This study discusses the Japaneseâ€™s ryosai (good wife) that depicted in Pramoedya Ananta Toerâ€™s novel â€œGadis Pantaiâ€. The similarities between Japanese ideal value of wives from Edo era and Javanese during Dutch colonizations can be found throughout the Toerâ€™s novel. This study conducted by using descriptive methods, by analyzing the ryosai value and then matching the findings to the novel. Both the society in the novel and the ryosai value limit the role of women as wives, giving them role in domestic level only based on their gender and biological function. The wives should dedicate their lives for their husbands, children and in-laws, and have no rights to educate and raise their children. This findings demonstrate the similarities of values between Japanese Edo era and Javanese Colonized era regarding womenâ€™s role in family and society.